Peran Penghargaan Memediasi Pengaruh Umpan Balik Terhadap Perilaku Kerja Tenaga Kesehatan Di RSUD Konawe Provinsi Sulawesi Tenggara, Indonesia - Rahman (STIKES Columbia Asia Medan, 2025)
The work behavior of health workers is a key factor in determining the quality of service and patient safety in hospitals. In healthcare organizations with high work demands, feedback and rewards are important instruments of human resource management to form positive work behaviors. However, empirical evidence on the role of rewards as a mediating variable in the relationship between feedback and work behavior of health workers, particularly in Indonesian regional hospitals, is limited. This study aims to analyze the influence of feedback on work behavior through the role of reward mediation in health workers at Konawe Hospital, Southeast Sulawesi Province, Indonesia. This study used a quantitative approach with a cross-sectional design. Data was collected through a survey using a structured questionnaire based on the Likert scale of 170 health workers with ASN status at Konawe Hospital. The sampling technique used a combination of purposive and accidental sampling. Data analysis was carried out with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS software version 4.0. The results showed that rewards had a positive and significant effect on work behavior (β = 0.579; t = 10.308; p = 0.000), and feedback had a positive and significant effect on rewards (β = 0.805; t = 25.851; p = 0.000). In addition, feedback also had a positive and significant effect on work behavior through rewards (β = 0.466; t = 8.362; p = 0.000), which confirms the mediating role of rewards. There is an influence of appraisal on work behavior and feedback on awards and awards has been shown to significantly mediate the influence of feedback on the work behavior of health workers. These findings emphasize the importance of effective feedback management and an integrated reward system as a managerial strategy to encourage positive work behavior and improve the quality of health services in regional hospitals.